Singapore : Financial Sector Assessment Program-Technical Note-Fintech: Implications for the Regulation and Supervision of the Financial Sector. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2019)
This technical note examines the implications of fintech for the regulation and supervision of the Singaporean financial services sector. It provides an overview of the financial system with a focus on fintech developments. The note looks at not only fintech developments but also the institutional setup as well as Monetary Authority of Singapore's (MAS) approach to fintech. The MAS has so far managed to strike the right balance between innovation and safety and soundness. MAS has responded quickly to the challenges of fintech. The impact of fintech on the financial services sector has largely been internalized by financial institutions (FI). FIs are swiftly digitizing and modernizing their systems, products and business models. Because of their market knowledge and higher investment capacities, incumbent FIs are getting better at providing services and products by adopting new technologies or improving existing ones. The note also recommends that it is imperative to develop a cyber network map that considers both financial linkages and Information and Communications Technology connections and use it for cyber risk surveillance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet